Functions of Compounding in German Translation of Vladimir Nabokov’s “King, Queen, Knave”: A Comparative Analysis with Russian and English Versions - A. V. Melgunova (Научный диалог, 2024)
This article explores the role of compound words in the German translation of a literary text. The analysis is based on Vladimir Nabokov’s novel “King, Queen, Knave,” comparing the original Russian text, the author’s English version, and the German translation from English. The relevance of this study stems from the growing interest in Nabokov’s legacy as a bilingual writer, particularly concerning translation and the comparative analysis of his works across languages. The novelty of this research lies in identifying frequency patterns of structural-semantic correspondences between German compounds and their counterparts in the respective literary texts. The findings reveal three primary types of structural-semantic correspondences: 1) a direct equivalent of a single word in both English and Russian (30%); 2) an equivalent of an English compound and a Russian phrase (34%); and 3) an equivalent of phrases in both English and Russian (32%). Furthermore, the comparison between the German and English texts highlights a unique feature of the German translation — namely, the addition of components that clarify the meaning of words. As a result, complex words in the German text emerge, with defining components that specify their meanings compared to the lexical units in the English version.